Diabetes in Sports and Exercise Medicine - Jaggers, Jason R. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on exercise and physical activity research among people living with diabetes and covers a broad overview of exercise-related topics. These range from short-term effects of exercise and using daily activity measurements as vital signs in diabetes care centers to the health and fitness benefits of resistance and aerobic exercise training of all kinds, exercise prescription as a form of complementary medicine, as well as the challenges faced by children and/or adults regarding exercise programming at the community level. The goal was to cover a broad range of diabetes research, including all forms of diabetes mellitus across all life spans.